Medical Student Interpretation of Visual Art: Who's Got Empathy? [Version 2] - Samuel Sampson; Johanna Shapiro; John Billimek; Joel Shallit; Julie Youm (MedEdPublish, 2018)
Introduction: Physician empathy is a highly desired characteristic in clinical practice with benefits for both patients and doctors. Increasingly, medical educators have acknowledged the importance of empathy and sought effective ways of inculcating and strengthening this quality in medical students. However, empathy remains difficult to measure because of differing definitions and theoretical dimensions. Our goal was to develop a de novo visual Art scale, devised to evaluate empathetic response in medical students as well as a de novo Biosocial scale to measure medical student socioeconomic and experiential stress during childhood and adolescence; and to compare these exploratory measures to the reliable and well-validated Jefferson Scale of Empathy JSE).